(untitled) (Scientific journal of the Fergana State University, 2025)
The article studies the amount of chemical elements and biogeochemical properties in the humus surface horizon of mountain-brown soils and in the organs (root, leaves, bulb head) of medicinal plants black onion (Allium karataviense Regel), Severtsov’s fritillary (Fritillaria sewerzowii Regel). It is proven that in natural soil and climatic conditions of mountain-brown soils, where black onion grows, the content of microelements Sb, Cs is lower and Sc, Cr, Co is higher than in lithosphere clackers. Accumulation of cyclic and dispersed microelements was observed in the root of black onion (Allium karataviense Regel). The amounts of microelements in the organs of Allium karataviense Regel and Fritillaria sewerzowii Regel vary within the range of Cr 2.31-9.90, Co 0.073-0.057, Sb 0.009-0.089, Sc 0.035-0.400, Cs 0.024-0.240 mg/kg. The amounts of these elements in the upper layers of mountain brown soils vary within the range of Cr 61.3-67.2, Co 15.0-15.6, Sb 1.30-1.54, Sc 11.4-11.8, Cs 7.04-7.42 mg/kg.